2020
DOI: 10.32528/ipteks.v5i2.3656
|View full text |Cite
|
Sign up to set email alerts
|

Financial Performance Dan Market Share Pada Bank Umum Syariah Devisa Indonesia: Perspektif Teori Stakeholder

Abstract: Penelitian ini menggunakan analisis analisis teori stakeholder yang belum diterapkan dalam beberapa penelitian sebelumnya. Penelitian ini juga penting, karena bank perlu mendapatkan informasi tentang determinasi dampak pada market share, selama market share dijadikan sebagai kunci pertumbuhan perusahaan dan cerminan untuk para stakeholder dalam menilai financial performancenya. Berdasarkan latar belakang yang telah dibahas sebelumnya, peneliti melakukan penelitian ini bertujuan untuk memahami bagaimana financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
1
10
0
1
Order By: Relevance
“…Financial reports are instrumenting corporate responsibility to thestakeholder which is then used as a tool in decision making. Fuadah and Hakimi (2020) state that financial performance is an economic indicator that represents a form of corporate responsibility to its stakeholders, stakeholder satisfaction is determined by how the company acts to provide it. Accordign to Beaulieu et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial reports are instrumenting corporate responsibility to thestakeholder which is then used as a tool in decision making. Fuadah and Hakimi (2020) state that financial performance is an economic indicator that represents a form of corporate responsibility to its stakeholders, stakeholder satisfaction is determined by how the company acts to provide it. Accordign to Beaulieu et.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of financial reports can be affected by accounting estimates (Ayunku & Owekee 2019;Ivana, Sanja, & Ivana, 2016;Ghos, & Siriviriyakul, 2019) which will eventually be used bystakeholder as a basis for making decisions. Fuadah and Hakimi (2020) state that financial performance is an economic indicator that represents the form of a company's response tostakeholder, bearing in mind that the benefits desired by stakeholders are determined by how the company acts to meet their satisfaction. The quality of financial reports is a necessity for users to be able to help them assess the overall performance of the entity and be able to make useful decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rahman's research also found that NPF, BOPO, and CAR together affected market share (Rahman, 2016). His research also states that ROA, NPF, FDR, and BOPO simultaneously affect market share (Fuadah & Hakimi, 2020).…”
Section: Simultaneous Influence Of Car Roa Npf and Fdr On The Market ...mentioning
confidence: 99%
“…Upgrade market share Banks are closely related to marketing. The marketing area reflects how customers determine the amount of their value for something they want (Harisson and Wicks in ( (Fuadah & Hakimi, 2020) so, how market share increasing company influenced by the success in providing value to the customers stakeholder. (product, price, place, promotion) to attract customers and develop market share for the company's products.…”
Section: Strategy Digitalmentioning
confidence: 99%